Pengaruh kepemimpinan kepala sekolah dan kinerja guru terhadap prestasi akademik siswa sekolah dasar negeri - Yohanah , Yohanah (ARKA INSTITUTE, 2022)
The purpose of this study was to analyze the effect of principal leadership on student academic achievement, the effect of teacher performance on student academic achievement, and the effect of principal leadership and teacher performance together on student academic achievement. This research approach is non-experimental quantitative. The population is all State Elementary School teachers in Sukasari District with 120 teachers, and the sample size is determined by 30% of the population, namely 36 people. Data collection techniques using a questionnaire. Analysis of the results of the study used descriptive statistics, simple regression, and multiple regression with SPSS Windows Version 26. Descriptively, the results showed that the leadership of the principal in SD Negeri in Sukasari District was included in the good category with a score of 2,247, teacher performance was in the very good category with a score of 2,247. 2,269 academic achievements of students are in the good category with an average of 1,995. With simple regression analysis, it is known: there is a positive and significant influence of principal's leadership on academic achievement of elementary school students in Sukasari District by 58.0%, teacher performance has a positive and significant effect on student academic achievement with a coefficient of determination of 48.9%. The results of multiple regression analysis showed that there was a positive and significant joint influence on the principal's leadership and teacher performance on the academic achievement of the Sukasari District Elementary School students with a coefficient of determination of 61.8%.